Seroprevalence of Subclinical HEV Infection in Healthy Pregnant Urban Dwellers of Bangladesh: Identification of Possible Risk Factors (Journal of Enam Medical College, 2018)
Background: Hepatitis caused by hepatitis E Virus (HEV) is not uncommon in developing countries. It is usually a self-limiting conferring immunity against subsequent infection. However, HEV infection during pregnancy results in varying degree of morbidity, often fatal. The present study was designed to find out the seroprevalence of subclinical HEV infection during pregnancy at different trimesters without history of hepatitis.Materials and Methods: A total 255 asymptomatic healthy pregnant women of three trimesters (85×3=255) with no history of jaundice were included in this cross-sectional study. The subjects were sub-grouped according to socioeconomic status and education level. HEV IgG antibody in serum was determined by enzyme linked immunosorbent assay (ELISA). Results were expressed as number (percent). Chi-square, Odds Ratio and 95% CI were calculated as applicable. Data analyses were carried out using statistical package for social science for Windows Version 15.0. A p